Discovery of differentially expressed lncRNAs in porcine ovaries with smaller and bigger litter size - Duan, Saixing; Li, Falei; Meng, Libing; Cheng, Shimei; Shi, Huangqi; Qu, Yingjie; He, Chaoyue; Gao, Shengyu; Li, Jian; Sun, Shiduo; Liu, Yong; Xu, Gaoxiao (Frontiers in Genetics, 2025)
IntroductionThe number of litters is an important reproductive trait, which is one of the main indicators reflecting the production level and economic benefit of the pig farm. As an important reproductive organ of female mammals, the ovary is controlled by a complex transcription network of coding and non-coding genes to undergo a series of biological processes during each estrus cycle, thereby regulating the reproductive capacity of the sow. However, these molecular regulation mechanisms affecting sow litter size are still unclear.MethodsRegarding the non-coding molecular regulatory mechanisms in ovarian function with smaller and larger litter size (SLS and LLS), we investigated the expression profile of lncRNA in pig SLS and LLS samples. Total RNAs from porcine ovaries were used to construct libraries using Ribo-Zero RNA sequencing method.ResultsHere we profiled the expression of lncRNA in porcine ovaries with SLS and LLS, and identified a total of 3,556 lncRNA candidates, of which 96 were upregulated lncRNA and 206 were downregulated lncRNA when comparing LLS to SLS. In addition, a competitive endogenous RNA (ceRNA) network was constructed, and it was found that lncRNAs LOC100513133 and LOC102168075 may serve as ceRNAs containing potential binding sites for miR-26b, let-7g and miR-125b.DiscussionThese results demonstrate that lncRNAs may play roles in modulating porcine litter size.